Metal-insulator Transition in \({}^{70}\)Ge: Ga Semiconductor by Applying the Scaling Laws (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
In this article, we focus on the scaling theory of Abraham et al. without and with a magnetic field on the metallic side of the Metal-Insulator Transition (MIT) for the three-dimensional system \({}^{70}\)Ge: Ga, at very low temperatures. In particular, we have determined the zero temperature conductivity critical exponent when the MIT transition occurs with the variation of the impurity concentration \((υ=0.503)\) and with the application of a magnetic field \((υ=1.06)\). We have also estimated the critical magnetic field \(B_C\) that separates the metallic behavior \((BB_C)\). The data are for a \({}^{70}\)Ge: Ga sample prepared and reported by Itoh et al., Physical Review Letters 77 (1996), 4058 and Watanabe et al., Physical Review B 60 (1999), 15817.
Keywords: \({}^{70}\)Ge; Ga semiconductor; Scaling theory; Low temperature; Magnetic field; Metal-insulator transition; Metallic electrical conductivity; Transport properties; Localization